(3QSGdI YdI GdMcIs - (3Mcje RGg, eMeOs
(3ChdgG (B:s
(3GdMeO dMcje Ndb GdOGA deG cGfJ GdYdI GdeYQhaI HGdMcI cKjQI GdhbhY hTOjOI GdCPjI ddCHOGf CQOJ Cf GMQQ QSGdI aj CSHGHgG heYGdLJgG ef GdcJH GdTQjaI hGdcfGfjT GdfajSI s
(3BNQgG (B:s
(3hbO ojDeQ CUMGH GdMcI HONhd GdMeGe hGdUHQ aj GdHjJ GdMGQ MJi jMei HOfg Ke jNQL ajJeVeV HGdeGA GdHGQO hjSJfTb efg Ke jLdS gPG BNQ GdQSGdIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdWHs